2009
DOI: 10.1002/jms.1552
|View full text |Cite
|
Sign up to set email alerts
|

Correct identification of oxidized histidine residues using electron‐transfer dissociation

Abstract: Oxidative modification to the side chain of histidine can noticeably change the collision-induced dissociation (CID) pathways of peptides containing this oxidized residue. In cases where an oxidized peptide consists of two or more isomers differing only in the site of modification, oxidation to histidine usually causes the other oxidized sites to be mis-assigned in CID spectra. These spectral mis-assignments can sometimes be avoided by using multiple stages of MS/MS (MS n ) or via specially-optimized liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Results-There can be variation in the fragmentation chemistry of oxidized versus unoxidized peptide isomers during the collision-induced dissociation, which can potentially confound the results in absolute terms (35,36,43,44). Such variations can also lead to negative bias, some example cases are shown by negative values of the RC (Table I).…”
Section: Sensitivity Of Data To Side Chain Chemistry and Reproducibilmentioning
confidence: 99%
“…Results-There can be variation in the fragmentation chemistry of oxidized versus unoxidized peptide isomers during the collision-induced dissociation, which can potentially confound the results in absolute terms (35,36,43,44). Such variations can also lead to negative bias, some example cases are shown by negative values of the RC (Table I).…”
Section: Sensitivity Of Data To Side Chain Chemistry and Reproducibilmentioning
confidence: 99%
“…Initial uses of HRPF were limited in spatial resolution to the size of a proteolytic peptide, as the amount of oxidation of any individual amino acid within the peptide could not be accurately quantified by CID [8-10]. As sub-microsecond HRPF technologies such as Fast Photochemical Oxidation of Proteins (FPOP) [3] and pulsed electron beam radiolysis [11] began to allow for heavier oxidation of proteins, the need to quantitate isomeric peptide oxidation products became even more pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because the dissociation chemistry of each oxidized isomer can be very different during CID, which gives rise to complicated spectra that are easy to mis-interpret [49,50]. This problem can be overcome if specialized LC separation conditions are employed to fully separate each oxidized isomer, but these LC conditions must be optimized for each isomer mixture, something that is prohibitive when multiple samples must be analyzed.…”
Section: Oxidationmentioning
confidence: 95%
“…This problem can be overcome if specialized LC separation conditions are employed to fully separate each oxidized isomer, but these LC conditions must be optimized for each isomer mixture, something that is prohibitive when multiple samples must be analyzed. Again, because ETD is less sensitive to side chain chemistry, this dissociation technique can be used to accurately identify oxidation sites for peptide isomers upon dissociating them simultaneously [50]. It has been found that oxidized peptide isomers tend to dissociate in similar manners during ETD, thereby avoiding the mis-interpretations that are common in CID of such isomers.…”
Section: Oxidationmentioning
confidence: 98%